The Response of Corneal Endothelial Cells to Shear Stress in an In Vitro Flow Model. (27th November 2021) - Duan, Sujuan; Li, Yingjie; Zhang, Yanyan; Zhu, Xuan; Mei, Yan; Xu, Dongmei; Huang, Guofu
Abstract : Purpose . Corneal endothelial cells are usually exposed to shear stress caused by the aqueous humour, which is similar to the exposure of vascular endothelial cells to shear stress caused by blood flow. However, the effect of fluid shear stress on corneal endothelial cells is still poorly understood. The purpose of this study was to explore whether the shear stress that results from the aqueous humour influences corneal endothelial cells. Methods . An in vitro model was established to generate fluid flow on cells, and the effect of fluid flow on corneal endothelial cells after exposure to two levels of shear stress for different durations was investigated. The mRNA and protein expression of corneal endothelium-related markers in rabbit corneal endothelial cells was evaluated by real-time PCR and western blotting. Results . The expression of the corneal endothelium-related markers ZO-1, N-cadherin, and Na + -K + -ATPase in rabbit corneal endothelial cells (RCECs) was upregulated at both the mRNA and protein levels after exposure to shear stress. Conclusion . This study demonstrates that RCECs respond favourably to fluid shear stress, which may contribute to the maintenance of corneal endothelial cell function. Furthermore, this study also provides a theoretical foundation for further investigating the response of human corneal endothelial cells to the shear stress caused by the aqueous humour.